1979
DOI: 10.1098/rspa.1979.0046
|View full text |Cite
|
Sign up to set email alerts
|

Frictional interactions between chip and rake face in continuous chip formation

Abstract: A transparent sapphire cutting tool is used to study directly the frictional interactions occurring at the chip–tool interface. The investigation deals with the orthogonal cutting of single phase, face-centred cubic materials, in air and in vacuum. The investigation brings out two points of importance. First, although there is intimate contact between the chip and the tool in the immediate vicinity of the cutting edge, there is relative movement at the chip–tool interface with little or no adhesive transfer of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(31 citation statements)
references
References 11 publications
2
29
0
Order By: Relevance
“…Oxygen has a significant influence on cutting mild steel and this is attributed to the reduction of gross adhesion of the chip at the rake face (Rowe and Smart 1963, 1964-1965, 1966-1967Rowe et al 1976). However, apparently anomalous effects have been noted when machining non-ferrous materials such as aluminium and copper, where oxygen seems to increase the cutting forces (Williams 1975;Wright et al 1979;Smart 1966-1967;Doyle et al 1979;Doyle and Horne 1980). This was explained by supposing that the tool would be subjected to the rubbing action of regions of oxide on the chip which might be sufficiently abrasive to remove the contaminant film on the tool resulting in high metallic contact (Williams and Stobbs 1979).…”
Section: Chapter 4 Utilisation Of Environmental Friendly Gaseous and mentioning
confidence: 95%
See 1 more Smart Citation
“…Oxygen has a significant influence on cutting mild steel and this is attributed to the reduction of gross adhesion of the chip at the rake face (Rowe and Smart 1963, 1964-1965, 1966-1967Rowe et al 1976). However, apparently anomalous effects have been noted when machining non-ferrous materials such as aluminium and copper, where oxygen seems to increase the cutting forces (Williams 1975;Wright et al 1979;Smart 1966-1967;Doyle et al 1979;Doyle and Horne 1980). This was explained by supposing that the tool would be subjected to the rubbing action of regions of oxide on the chip which might be sufficiently abrasive to remove the contaminant film on the tool resulting in high metallic contact (Williams and Stobbs 1979).…”
Section: Chapter 4 Utilisation Of Environmental Friendly Gaseous and mentioning
confidence: 95%
“…Doyle et al (1979), Wallace and Boothroyd (1964) identified intimate contact between the chip and the tool over a region adjacent to the immediate vicinity of the cutting edge. This intimate contact is known as the sticking region.…”
mentioning
confidence: 98%
“…F f is approximately 6.67 N. It is possible to check this value with Merchant and Zlatin's (Doyle et al 1979) nomograph for frictional force. However, the values for F h and F v are so small the extreme limits of the nomograph are being tested so it is difficult to give an accurate value for F f , it is certain that this value is below 10 N which is in close agreement with the calculated answer.…”
Section: Micromachiningmentioning
confidence: 98%
“…Thus, it might be suggested that tight curl is an integral part of the primary deformation due to friction interactions between chip and tool edge. The process of continuous chip formation is not uniquely defined by the boundary conditions in the steady state and that the radius of curl may depend on the build-up of deformation at the beginning of the cut (Doyle et al 1979). A treatment of primary chip formation at the microscale is presented, which considers chip curl as a series of heterogeneous elements in continuous chip formation at the microscale.…”
Section: Chip Formationmentioning
confidence: 99%
See 1 more Smart Citation